A Review Study on Educational Interventions Promoting Sexual Health of Children Under 12 Years - Zahra Barimani Aboksari; Jila Ganji; Nouraddin Mousavinasab; Maedeh Rezaei; Soghra Khani (Mazandaran University of Medical Sciences, 2020)
Context: Most children do not receive sexual education. This ignorance may adversely affect different dimensions of one's sexual health. However, talking to children about this issue constantly but briefly can have positive impacts on their relationships and sexual health. This study aimed at reviewing different types of educational interventions related to the sexual health of children under 12 years. Evidence Acquisition: In this narrative review, Google Scholar, PubMed, Scopus, Science Direct, and Web of Science databases were searched using the following keywords: "sex education", "sexual education", "sexual health", "sexual training and children". Two researchers (Zahra Barimani Aboksari and Maedeh Rezaei) searched articles related to children's sexual health up to December 2018.  Results: The relevant articles were categorized into 4 groups: 1. children-focused interventions: sexuality education coaching program, child sexual abuse prevention program, body image, and decrease in gender-typed remarks; 2. parent-focused interventions: child sexual abuse prevention education and child sexual training; 3. children- and parent-focused interventions: HIV/AIDS prevention program and saving sex for later; and 4. the impact of culture and religion.  Conclusions: Sexual health in childhood can guarantee the sexual health of the coming years of life; therefore, it is worthwhile to pay attention to this issue and set plans and policies in familial and social aspects based on the interventions mentioned in this study.